SOCIALIZATION OF INTEGRATED QUALITY MANAGEMENT IN ISLAMIC BOARDING SCHOOL EDUCATION FOR USTADZ AND SANTRI IN KEDUNGJERUK VILLAGE, KARAWANG REGENCY - Permana, Hinggil; Wahyudin, Undang Ruslan; Nurlailasari, Ella; Irwansyah, Ridwan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Islamic boarding school education is one of the traditional educational institutions that has an important role in maintaining and developing religious, cultural, and social values in the community. In Kedungjeruk Village, Cibuaya District, Karawang Regency, Islamic Boarding School is one of the educational centers that plays a vital role in the formation of student character and in the development of religious science. As an education center that is crucial in shaping the character of students and expanding religious knowledge, integrated quality management is an essential approach to improve the quality of education in the Islamic Boarding School. Through the Socialization of Integrated Quality Management, the ustadz and santri were introduced to the concepts, principles, and practices of integrated quality management, with the aim of deepening the understanding of the importance of integrated quality management in improving the quality of education in Islamic boarding schools. Socialization activities cover various aspects, from concepts to performance measurement and quality evaluation, involving active participants in discussions and debates on the implementation of integrated quality management in the context of Islamic boarding schools. It is hoped that a deeper understanding of integrated quality management will help the ustadz and students contribute positively in efforts to improve the quality of education at the Kedungjeruk Village Islamic Boarding School, ensuring sustainable growth, and provide quality education in accordance with the demands of the times.